Perlindungan Hukum Terhadap Notaris Dalam Melaksanakan Rahasia Jabatan Terhadap Akta Yang Dibuatnya Terkait Sengketa Internal Para Pihak Di Pengadilan - Yoseph Freinademetz Kantar; Jelly Nasseri; Anriz Nazruddin Halim (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
A notary is a public official who is only authorized to make an authentic deed regarding all actions, agreements, and stipulations required by general regulation or by an interested party who is required to be stated in an authentic deed, guarantees the certainty of the date, keeps the deed, and gives Grosse, copies, and the quotation, as long as the making of the deed by general regulation is not assigned or excluded to other officials or people. This research uses Philipus M. Hadjon's legal protection theory and Sudikno Mertokusumo's legal certainty theory. The normative juridical study uses literary or secondary data from primary, secondary, and tertiary legal sources. The Statute Approach, Conceptual Approach, Analytical Approach, Case Approach, and the method of identifying and inventorying positive legal rules, literature, books, journals, and other legal sources are utilized for research. Analyzing legal documents involves legal interpretation, systematic interpretation, and legal construction. The study found that a Notary is a public authority who facilitates community legal actions. The Law on Notary Positions encompasses most legal ties in society. Protection and legal certainty for Notaries summoned as witnesses in criminal proceedings, notably on their obligation to keep their positions secret. As said earlier, a Notary is a trusted position that must be kept hidden.